Additions to the knowledge on the genus Tiphia Fabricius (Hymenoptera: Tiphiidae: Tiphiinae) from India with the description of ten new species - Hanima, Raveendran K.p.; Kumar, P. Girish; Hegde, Vishwanath D. (Zootaxa, 2022)
The genus Tiphia Fabricius from India was studied, resulting in the description and illustration of five new species based on females, Tiphia (Tiphia) bijui Hanima & Girish Kumar sp. nov., T. (T.) novus Hanima & Girish Kumar sp. nov., T. (T.) rajeevani Hanima & Girish Kumar sp. nov., T. (T.) sahyadriensis Hanima & Girish Kumar sp. nov., and T. (T.) venkataramani Hanima & Girish Kumar sp. nov., and five new species based on males, T. (Punctotiphia) chareshi Hanima & Girish Kumar sp. nov., T. (T.) davidrajui Hanima & Girish Kumar sp. nov., T. (T.) hyalina Hanima & Girish Kumar sp. nov., T. (T.) kurumba Hanima & Girish Kumar sp. nov., and T. (T.) shajii Hanima & Girish Kumar sp. nov., from India. The male of T. lyrata Magretti, is newly reported with descriptions and illustrations. Seven species are reported for the first time from India. Range extensions of several species to various states of India are also augmented here. The male genitalia of 16 species were dissected and studied. A modified key to species of Tiphia from the Indian subcontinent is provided. An updated distributional checklist from India is also provided.